2004
DOI: 10.1016/j.clpt.2003.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in drug plasma concentrations of an extensively bound and highly extracted drug, propofol, in response to altered plasma binding

Abstract: During cardiopulmonary bypass, a significant increase in the concentration of unbound propofol occurred without alteration in the total propofol concentration in blood. The effect of the changes of propofol's protein binding on its kinetics was consistent with the predictions based on the well-stirred model of hepatic elimination for an intravenously infused high-clearance drug. Our finding on propofol pharmacokinetics may be the first example demonstrating the theoretic prediction of the well-stirred model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 35 publications
6
74
0
8
Order By: Relevance
“…Propofol is a short-acting drug with a large volume of distribution and high total body clearance. 1 Since the hepatic extraction ratio of propofol is high 2 and urinary excretion of unchanged propofol is minimal, 3 hepatic metabolism is considered the primary elimination pathway and drug metabolism thus depends on liver blood flow (LBF).…”
mentioning
confidence: 99%
“…Propofol is a short-acting drug with a large volume of distribution and high total body clearance. 1 Since the hepatic extraction ratio of propofol is high 2 and urinary excretion of unchanged propofol is minimal, 3 hepatic metabolism is considered the primary elimination pathway and drug metabolism thus depends on liver blood flow (LBF).…”
mentioning
confidence: 99%
“…However changes in plasma protein binding were shown to have very little clinical relevance, [16][17][18] except for a small group of drugs, such as propofol, that are extensively protein bound ([96%) and have a very large volume of distribution. 19,20 This was clearly demonstrated when sudden cardiopulmonary bypass hemodilution resulted in a twofold increase in the unbound propofol with an immediate decrease in BIS values, despite propofol total plasma concentration remaining unchanged. 21 Compared with the Caucasians, the Chinese subjects were shown to have different plasma protein binding to drugs, as they possess lower a-1-acid glycoprotein plasma concentrations, a glycoprotein shown to accelerate recovery from drugs by increasing protein binding.…”
Section: Discussionmentioning
confidence: 99%
“…Data for each treatment group are presented as the mean and standard deviation measured under similar operative conditions. 27,[34][35][36][37] It is clear that steady state conditions were not achieved, but it is also clear that steady state conditions for propofol cannot reasonably be anticipated within the context of cardiac surgery. We suggest that a significant reduction in the variance of propofol concentrations in the absence of steady state conditions will require monitoring of the concentration achieved during the course of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…24 The authors estimated a whole-blood propofol concentration of 3.7 lg Á mL -1 based on other clinical studies with similar operative procedures. [26][27][28] We previously found that a 2 to 2.5 mg Á kg -1 bolus of propofol followed by an infusion of 200 lg Á kg -1 Á min -1 produced drug concentrations associated with increased antioxidant capacity (8.2 ± 2.1 lg Á mL -1 ) but showed signs of intraoperative cardiac depression compared with conventional propofol or isoflurane anesthesia maintenance. 29 More recently, increasing propofol anesthetic maintenance from 60 to 120 lg Á kg -1 Á min -1 intraoperatively was associated with a reduction in biomarkers of cardiac injury and oxidative stress, although the range of values was consistent with those expected during cardiac surgery.…”
Section: Résumémentioning
confidence: 99%